Approches réflexives sur l'accompagnement pédagogique au sein d'une communauté web 2.0 d'apprenants de langues - Anthippi Potolia; Katerina Zourou (Centre National d'Enseignement à Distance, 2019)
This contribution explores the strengths and limitations of online language tutoring in an informal digital context, as experienced by a group of teachers of French as a foreign language. Our study aimed to encourage reflexivity on feedback and error correction practices in web 2.0 language learning communities (namely Busuu and Duolingo), which are self-regulated, participatory and less controlled, less structured situations than the language classroom. Twenty-one students attended one of these communities for six weeks, playing the dual role of learner of an L2 and tutor of French. Participants recorded their actions, observations and reflections in a diary. The analysis shows that the teachers were involved in both peer feedback and correction and that they became accountable for their tutoring practice, leading them to (re)assess evidences about their profession. Moreover, the ambiguity of roles in these communities has often generated tensions as to the legitimacy of the act of correcting and a certain disengagement linked to the detached character and the lack of sustainable interaction.